Transmission of Japanese government bond and swap markets under negative interest rate policy. (9th September 2020) - Ito, Takayasu
The transmissions from Japanese government bond (JGB) to swap in the maturities of four, five and ten years are confirmed under the regime of negative interest rate policy before the introduction of yield curve control (YCC). This means that the market function only works in the maturities of four, five and ten years. After the Bank of Japan (BOJ) introduces YCC policy under negative interest rate policy, the transmissions from JGB to swap are confirmed in all maturities except for two years. This means that the market function works in the maturities of three, four, five, seven and ten years under YCC policy with negative interest rate policy regime. Comparing before and after the introduction of YCC, the transmissions from JGB to swap are stronger after the introduction of YCC. The market function gradually recovers with the introduction of YCC because market participants assume that long-term interest rates will move above the level of 0% with more volatilities. More than 90% of JGBs are held by domestic investors. Thus, JGB and swap markets are less influenced by other international markets.